Pregnancy after Endometriosis: Maternal and Neonatal Outcomes according to the Location of the Disease - Uccella, Stefano; Manzoni, Paolo; Cromi, Antonella; Marconi, Nicola; Gisone, Baldo; Miraglia, Andrea; Biasoli, Sara; Zorzato, Pier Carlo; Ferrari, Stefania; Lanzo, Gabriele; Bertoli, Francesca; Capozzi, Vito Andrea; Gallina, Davide; Agosti, Massimo; Ghezzi, Fabio (American Journal of Perinatology, 2019)
Objective To systematically evaluate pregnancy and labor course, obstetrical complications, and maternal and neonatal outcomes in women with endometriosis, stratifying according to the specific location of the disease.Study Design We retrospectively analyzed our prospectively maintained obstetrical database from January 2011 to August 2014 to identify all women with a previous histological diagnosis of endometriosis who delivered at our institution (cases). We divided the cases according to the specific location of the disease (deep infiltrating endometriosis, ovarian endometriosis, and peritoneal endometriosis). As controls, we identified all unaffected women who delivered in the year 2013. To avoid the confounding effect of parity, we limited our analysis to nulliparous women.Results A total of 118 nulliparous women with endometriosis and 1,690 nulliparous controls were identified. Women with endometriosis were significantly older, had a lower body mass index, and had a higher incidence of assisted reproductive technology. The duration of pregnancy was significantly shorter among women with endometriosis. A higher incidence of placenta previa (3.4 vs. 0.5%; p = 0.006), hypertension (11 vs. 5.9%; p = 0.04), cesarean section (41.5 vs. 24.2%; p < 0.0001), and vacuum delivery (10.1 vs. 2.9%; p = 0.006) was found in women with endometriosis. Neonatal outcomes were similar between groups. The incidence of placenta previa in patients with deep endometriosis was 11.7 versus 0.5% among controls (p < 0.0001), whereas in women with ovarian and peritoneal endometriosis, it was similar to the controls.Conclusion Women with endometriosis have a higher incidence of vacuum delivery, cesarean section, and placenta previa compared with unaffected women. The higher risk of placenta previa is attributable exclusively to women with deep endometriosis. Neonatal outcomes are unaffected by the presence of the disease.
Keywords: endometriosis; pregnancy; deep endometriosis; endometrioma; neonatal outcomes; maternal outcomes